Watergate and the resignation of President Nixon - Honders, Christine (American history (Lucent Books), 2019)
Presents a short examination of the presidency of Richard Nixon and the Watergate scandal which led to Nixon resigning. Discusses the so-called "Watergate Effect" and the legacy that the scandal has had on American media and political consciousness.